Wrist Function Test and Its Use to Assess Treatment Efficacy in Ischemic Stroke Survivors—A Pilot Study - Dmitry Skvortsov; Danila Lobunko; Anna Lobunko; Nina Belonovskaya; Galina Ivanova (Diagnostics)
Stroke is a major health issue causing high mortality and disability rates. Around 80% of stroke survivors experience impaired upper limb function, which is typically evaluated clinically. Functional electrical stimulation (FES) may help in motor function recovery. This study aimed to create an objective test of wrist flexion and extension functions and to assess the use of such a test in evaluating the efficacy of conventional rehabilitation therapy, alone and in combination with FES, in patients with a paretic upper limb. Background/Objectives: A total of 55 subjects were involved: 15 healthy volunteers and 40 post-stroke patients. The patients were split into two groups: one receiving only conventional rehabilitation (control group) and another receiving both conventional and FES therapies (FES group). Methods: Inertial sensors measured wrist flexion and extension parameters before and after the study treatment. Results: Both groups showed improvement based on the ARAT and FMA-UE scales. Normative values were established in the healthy group, revealing interhemispheric asymmetry. The wrist motion amplitudes and phases in both patient groups differed significantly from the healthy group. Initially, the paretic side had a 40-degree reduction compared to healthy subjects, while the non-paretic side showed a 10–17-degree decrease. After treatment, the FES group demonstrated a 4–10-degree increase in the wrist motion amplitude on the paretic side. The phase parameters did not change significantly in either group. Conclusions: The developed wrist flexion–extension test was shown to be objective and sensitive. The FES treatment improved the movement amplitude, although it did not alter the temporal structure of motion in both patient groups.